Moving from control to elimination of Visceral Leishmaniasis in East Africa - Makau-Barasa, Louise Kathini; Ochol, Duncan; Yotebieng, Kelly A.; Adera, Cherinet B.; de Souza, Dziedzom K. (Frontiers in Tropical Diseases, 2022)
Visceral leishmaniasis (VL) is arguably one of the deadliest neglected tropical diseases. People in poverty bear the largest burden of the disease. Today, the largest proportion of persons living with VL reside in the Eastern African countries of Ethiopia, Kenya, Somalia, South Sudan, and Sudan. These East African countries are among the top 10 countries reporting the highest number of cases and deaths. If left undiagnosed and untreated, VL almost always results in death. Subsequently, there is a need for integrated efforts across human, animal, and vector-control programs to address the scourge of VL in East Africa. In the East African region, the challenges including socio-cultural beliefs, poor health system, political instability, and limited epidemiological understanding impede the implementation of effective VL control strategies. The availability of funding, as well as diagnostics and treatment options, are also devastatingly limited. Furthermore, given the realities of climate change and population movement in the region, to effectively address the scourge of visceral leishmaniasis in East Africa, a regional approach is imperative. In this paper, we highlight some of the key challenges and opportunities to effectively move towards an effective control, and eventually elimination, of VL in East Africa. To do this, we underline the need for a fully integrated program in East Africa, inclusive of effective diagnostics and treatment, to effectively reduce and eliminate the burden of VL in the region, subsequently paving the way to achieve global elimination goals.